Analysis Of Waiter Performance In Improving Service Quality At Azure Bar Hotel Conrad Bali - Rondonuwu, Jonathan; Takaendengan, Mita Erdiaty; Lewan, Yurike Sintia (Politeknik Sahid, 2024)
Purpose: To improve the performance of waiters, this research is based on frequent errors in serving food and drinks, which cause delays in service. This error occurs because the waiter does not always repeat the order or ask about the guest's allergies, and is not precise in serving drinks. In addition, checking guest satisfaction based on order of arrival is also a problem. Waiters should be more proactive in meeting guests' needs.Methods: The research method used is descriptive qualitative with data collection through observation, interviews and literature study.Implikasi: The research showed that the waiters' performance was good but not optimal, with 56.25% of the 16 observation points carried out well, while 43.75% were still rarely carried out. From the interviews, it was concluded that the waiters at Azure Bar were friendly, responsive and professional, and played an important role in creating a satisfying experience for customers and maintaining the reputation of the place. In conclusion, the waiter's performance is quite good but can still be improved to ensure guest satisfaction and comfort.